2000
DOI: 10.1161/01.cir.101.4.366
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Platelet Glycoprotein IIb/IIIa Inhibition With Eptifibatide in Patients With Non–ST-Elevation Acute Coronary Syndromes

Abstract: Background-In the PURSUIT trial, eptifibatide significantly reduced the 30-day incidence of death and myocardial infarction relative to placebo in 9461 patients with an acute coronary syndrome (unstable angina or non-Q-wave myocardial infarction). Methods and Results-We conducted a 2-part prospective economic substudy of the 3522 US patients enrolled in PURSUIT: (1) an empirical intention-to-treat comparison of medical costs (hospital plus physician) up to 6 months after hospitalization and (2) a lifetime cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 6 publications
3
84
0
1
Order By: Relevance
“…These two exceptions isolated one country from the trial and estimated costs, effects and cost-effectiveness solely using patient data from that country. 194,195 Sensitivity analysis Table 12 describes the different sensitivity analysis approaches used in the studies included in the present review. Details of those variables, which have the potential to vary by location, which were assessed in these analysis are also provided.…”
Section: Table 11 Details Of the Basis Of The Cost Analysis In Econommentioning
confidence: 99%
See 1 more Smart Citation
“…These two exceptions isolated one country from the trial and estimated costs, effects and cost-effectiveness solely using patient data from that country. 194,195 Sensitivity analysis Table 12 describes the different sensitivity analysis approaches used in the studies included in the present review. Details of those variables, which have the potential to vary by location, which were assessed in these analysis are also provided.…”
Section: Table 11 Details Of the Basis Of The Cost Analysis In Econommentioning
confidence: 99%
“…First, only two studies 194,195 assessed the representativeness of the study sample to the study population in the trial centres. If only a small proportion of patients are recruited into trials from amongst those eligible (i.e.…”
Section: Study Reportingmentioning
confidence: 99%
“…The study design proposed in our application involved 3 major components: (1) collection of empirical resource use data (all patients) and hospital cost data (US patients), (2) an intention-to-treat comparison of within-study medical costs, and (3) a lifetime cost-effectiveness analysis. The cost-effectiveness analysis used empirically collected study data to make projections of lifetime costs and life expectancy beyond the end of study follow-up.…”
Section: Overview Of Economic Analysesmentioning
confidence: 99%
“…The effectiveness of eptifibatide was based on all Western European patients: a 0.37% risk difference for survival and a 1.01% risk difference for MI-free survival at 6 months favouring eptifibatide. Using the modelling approach and life expectancy data detailed in a US paper using similar methods, 98 LYG were estimated. Using cost data from UK patients, the cost-effectiveness analysis showed that treatment with eptifibatide was dominant.…”
Section: Comparison With the Results Of Other Studiesmentioning
confidence: 99%